IMPLEMENTASI PENDIDIKAN NILAI (LIVING VALUES EDUCATION) DALAM PEMBELAJARAN IPS (STUDI TERHADAP PEMBENTUKAN KARAKTER ANAK DI TINGKAT SEKOLAH DASAR) - Sukitman, Tri; Ridwan, M (Profesi Pendidikan Dasar, 2016)
Information and communication technologies that facilitate the service of the man, in fact also accelerate the negative effects for the existence of values   that has evolved in this masyarakat. Pernyataan evidenced by the spread of violence committed on school-age children, sexual abuse, a lack of values   of decency against the old, free sex, abortion, and others. The spread of this phenomenon is inseparable from the development of information and communication technology that has now become the primary needs of a person. This research is categorized into field research (field research) were designed using qualitative approach with case study method (case study). The data collection techniques were used in this research through interviews, observation, field notes (field notes), study the documentation, and literature. Results of research conducted in SDN Batang-Batang Power I declare that there is some development programs educational value, including the value of education is integrated into the curriculum in 2013 (K-13) and the development of value by maximizing the role of parents in monitoring every activity of children in the home environment through liaison book. The book serves for monitoring the activities of children at home every day ranging from learning, prayer, reading the Koran, refined language (Enggi Bunten), and helping the elderly.